-37 - 3*(-2-12)=
=-37 -3 *(-24)=
=-37 +72= 35
(920-160):(-19)- (-100)-(+5)-(-1)=
=(+760):(-19)+100 -5 +1=
=-40 +101-5=
=-45+101= -56
(-336+33):(-3)+(-9)-(+99)+999=
=(-303):(-3)-9-99+999=
=101 -108 +999=
=1100-108= 992
[(-3)-(-40)]:37=
=(-3+40):37=
=37:37=1
[7-(+5)]* [-120-(+75)]=
=(7-5)*(-120-75)=
=2*(-195)=-390
-5*{[-72:[-24-(-10)+50]+36:(-6)}=
=-5*[-72:(-24+10+50)-6]=
=-5*[-72:(-24+60)-6]=
=-5*(-72:36-6)=
=-5*(-2-6)=
=-5*(-8)= 40
-12+12*{13-13*[-5-(-2)*3]-6}=
=-12+12*{13-13*[-5-(-6)]-6}=
=-12+12*{[13-13*(-5+6)]-6}=
=-12+12*[(13-13*1)-6]=
=-12+12*(0-6)=
=-12+12*(-6)=
=-12-72= -84